Comparison of Non-Gated vs. ECG-gated CT Angiography of Fontan Circulation in Patients with Implanted Stents in Pulmonary Branches - Marek Kardoš; Juraj Mikuláš; Ivan Vulev; Jozef Mašura (Acta Medica, 2017)
Background: Motion artifacts may degrade CT examination of Fontan pathway and hinder accurate diagnosis of in-stent restenosis. Purpose: We retrospectively compared ECG-gated multi-detector computed tomography (CT) with non-ECG-gated CT in order to demonstrate whether or not one of the methods should be preferred. Method: The study included 13 patients with surgically reconstructed Fontan pathway. A total of 16 CT examinations were performed between February 2010 and November 2015.The incidence of motion artifacts in Fontan pathway and pulmonary branches were analysed subjectively by two readers. The effective dose for each examination was calculated. Results: Just in one non-gated CT examination was evidence of motion artifact in distal part of left pulmonary artery. The mean normalized effective radiation dose was 2.33 mSv (±0.62) for the non-ECG-gated scans and 4.55 mSv (±0.85) for the ECG-gated scans (p ≤ 0.05). Conclusion: Non-gated CT angiography with single phase reconstruction significantly reduces radiation dose without loss of image quality compared with ECG-gated CT angiography.